Pengaruh Struktur Modal terhadap Nilai Perusahaan pada Perusahaan Jasa Sub Sektor Manufaktur yang terdaftar di Bursa Efek Indonesia - SINDI OKTAVIA; Rosyeni Rasyid (Financial Management Studies, 2023)
The aim of study is to examine the effect of Capital Structure measured by Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) to Firm Value in property and real estate sub-sector service companies listed on the Indonesia Stock Exchange. This study uses two control variables, namely firm size and market risk measured by Beta. The population in this study are 81 service companies in the property and real estate sub-sector that are listed on the Indonesia Stock Exchange between 2017-2021. The sample is determined by purposive sampling to obtain 187 companies. Type of data using secondary data obtained from www.idx.co.id. The analytical method used is multiple linier regression analysis. Based on the results of the study concluded that Capital Structure measured by Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) have negative effect on firm value in service companies in the property and real estate sub-sector